Progress in cryptology – AFRICACRYPT 2019 : 11th International Conference on Cryptology in Africa, Rabat, Morocco, July 9-11, 2019, Proceedings /: 11th International Conference on Cryptology in Africa, Rabat, Morocco, July 9-11, 2019, Proceedings. (2019) - Unknown
No abstract available